Konsep Hulu-Teben pada Permukiman Tradisional Bali Pegunungan/Bali Aga di Desa Adat Bayung Gede Kecamatan Kintamani Kabupaten Bangli, Bali - IGN Tri Adiputra; S Sudaryono; Djoko Wiyono; Ahmad Sarwadi (Faculty of Engineering, Universitas Gadjah Mada, 2016)
The research tries to explain the specific Hulu-Teben concept of Bayung Gede custom village as dialog result between the normative Hulu-Concept as a background knowledge with the phenomena of spatials system anomaly at Bayung Gede customvillage.The research utilized phenomenology paradigm of Hussrel where Hulu-Teben of custom village in general takes a role as background knowledge. It’s discussed with the macro spatial system of Bayung Gede custom village to show the uniqueness spatial as the architectural anomaly of mountain village. Deepening study of the anomaly above was done in gaining the community’s social-culture background/their local wisdom as thetranscendental consciousness. Further Hussrel emphasizes that the highest transcendental peak is obtained by doing the three steps of reduction, i.e : (i) a phenomenological reduction of all related information to get some empirical themes, such as ; (a) Upperengga Mala and (b) Tegak Paumahan, (ii) the eidetic reduction of the three empirical themes to generate the architecture concept and (iii) the final reduction is transcendental reduction to discovery the architecture local theory. In the context within the research of Bayung Gede custom village, the aim is only focused at the architecture concept.The research results show that Hulu-Teben concept of Bayung Gede custom village has adapted Hulu-Teben in general shown by existence of Para Kahyangan Desa (custom village religious indicator) as the appreciating expression form for community’s ancestor. On the other hand, there are some spatial anomalies as an additional and enriching the general Hulu-Teben concept. Those are related with their local wisdom, it’s not only for appreciating their ancestors (upper level of human being) but it’s also for : (i) the former king of Jaya Pangus and the queen of Ulun Danu Batur (upper level of human being but they’re not ancestors), (ii) the equal level of human being and (iii) lower level of human being (the plantation, the animal and other creature).Keyword : Hulu-Teben spatial “anomalies” Bayung Gede, Custom Village